Implementasi Sistem Penjualan Alat Laboratorium Menggunakan Metode Waterfall Berbasis Web - Kevin Kevin; Jefri Ramadhan; M. Diarmansyah Batubara (Program Studi Sistem Informasi, 2020)
This study aims to implement the laboratory sales system in Indonesia, especially in terms of the obstacles we face when selling. The analysis this time we use qualitative, where the process also uses the sales data input system from other laboratories using the waterfall method. The results of this analysis indicate that the implementation constraints of the laboratory equipment sales system have two systems, namely the online and offline system. The online system uses an order via the web, then order goods online. Meanwhile, the offline system must come directly to the store and order directly and input the system manually. This is what hampers a sales system to input sales results offline and the system will be developed automatically using the web so that sales increase.Keywords: Web, Waterfall, Sales System.